Pesantren and Community Development - Imam Toriqor Rahmansyah (Jurnal Syntax Transformation, 2023)
Islamic boarding schools as educational institutions with their own characteristics have a strategic value in coloring the pattern of education in Indonesia. There is an assumption that Islamic boarding schools are not just places to learn religious knowledge, more than that pesantren as a place to learn community life where all aspects of life are found in it. It is proven that the existing pesantren have experienced many advances in various fields, not only educational institutions but also as a forerunner of changes in society. Da'wah as a forum for community development can be done in various ways, and one of them is with Islamic boarding schools. The Global Era changes many things in terms of life. This is an important concern for pesantren as a challenge and opportunity, because until now pesantren is a part that acts as a concept and also a practice for (community development).